ZIF-67-derived Co3S4 quantum dot composite TiO2 heterojunction optoelectronic materials, methods, and applications

CN122878950APending Publication Date: 2026-10-09QINGDAO UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610896684.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-22
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

[0002]304不锈钢在海洋环境中极易发生腐蚀,引发严重的资源浪费与安全隐患

Benefits of technology

本发明通过实现零维Co3S4量子点在TiO2表面的原位均匀锚定,有效解决了量子点易团聚、界面结合力弱及易脱落的技术难题;利用两者优异的能带匹配构建高效异质结,在显著拓宽光谱响应范围的同时,大幅加速了界面光生载流子的定向迁移与分离,从而为海洋环境下的不锈钢等金属结构件提供兼具高光电防腐效率与长效稳定性的光生阴极保护新策略;具体:

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The application belongs to the field of photo-induced cathodic protection of metals, and particularly relates to a ZIF-67 derived Co3S4 quantum dot composite TiO2 heterojunction photoelectric material, a preparation method and application. The application uses zeolite imidazole framework-67 (ZIF-67) as a precursor, and through in-situ growth, zero-dimensional Co3S4 quantum dots are highly dispersed and firmly chemically anchored on the surface of TiO2, and a heterojunction interface with atomic-level strong chemical bonding is constructed. The specific surface area of the modified composite material is significantly increased, the effective band gap is reduced to 2.62 eV, and the visible light absorption range is greatly widened. The ideal band matching of the two phases constructs a high-efficiency built-in electric field, significantly reduces the heterojunction interface charge transfer impedance, realizes the high-speed directional migration of photo-generated electrons and completely suppresses the carrier recombination. Under the simulated marine environment, the material exhibits excellent and long-acting photo-induced cathodic polarization protection capability, and can effectively delay the oxidation and corrosion process of metals such as 304 stainless steel, and the maximum protection potential drop can reach 718 mV vs. SCE.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of photogenerated cathode protection of metals, specifically relating to a ZIF-67-derived Co3S4 quantum dot composite TiO2 heterojunction optoelectronic material, its preparation method, and its application. Background Technology

[0002] 304 stainless steel is highly susceptible to corrosion in marine environments, leading to serious resource waste and safety hazards. Traditional cathodic protection methods (sacrificial anode method and impressed current method) have limitations such as high anode consumption, high cost, and cumbersome subsequent maintenance and monitoring. Photogenerated cathodic protection technology, as a novel corrosion protection technology, utilizes the transfer of electrons generated by semiconductor materials under light to the metal surface, causing cathodic polarization of the metal to inhibit corrosion. It has significant advantages such as being light-driven, having zero energy consumption, and being environmentally friendly.

[0003] Titanium dioxide (TiO2) is one of the most commonly used photocathode materials for photocathode protection due to its high chemical stability, resistance to photocorrosion, and non-toxicity. However, TiO2 has a wide bandgap (approximately 3.2 eV), which means it can only respond to a very small portion of the ultraviolet light in the solar spectrum, resulting in low visible light utilization. At the same time, its internal photogenerated carrier recombination rate is high and its migration rate is slow, which greatly limits its photoelectric corrosion protection efficiency.

[0004] To address the aforementioned issues, constructing heterojunctions is an effective strategy for controlling their charge separation pathways. Quantum dot-modified TiO2 composites are one such method; however, existing materials still face numerous bottlenecks in their preparation and application. Due to the extremely high surface energy of cobalt tetrasulfide (Co3S4) quantum dots, they are prone to severe self-aggregation during traditional physical mixing or conventional in-situ deposition processes, resulting in the loss of the size effect and high activity sites characteristic of zero-dimensional materials. Furthermore, existing preparation methods often struggle to precisely control the substrate anchoring density and distribution uniformity of quantum dots on the TiO2 surface, and the bonding between the two relies primarily on weak physical adsorption, lacking strong chemical bonding. This not only leads to high interfacial impedance in the heterojunction and easy secondary recombination of photogenerated electrons upon transport to the TiO2 interface, but also causes the loaded quantum dots to easily detach or be chemically oxidized in long-term high-salt, high-flow-rate marine corrosive environments, resulting in rapid degradation of photocatheter protection performance. This has become the main technical bottleneck limiting the long-term stable corrosion protection of high-performance Co3S4 / TiO2 photoanode materials. Furthermore, there is still a lack of systematic and in-depth research on the microscopic growth mechanism, fine interface structure, and synergistic anti-corrosion mechanism of Co3S4 quantum dots on TiO2 surfaces. This has become the main technical bottleneck restricting the functional optimization of high-performance TiO2-based photoanode materials.

[0005] Therefore, developing a method to achieve in-situ, uniform, and tight anchoring of Co3S4 quantum dots on the TiO2 surface, and then constructing Co3S4 / TiO2 heterojunction materials with efficient directional charge transport channels, is a key technical path to achieve efficient photogenerated electron separation, broaden the spectral response range, and improve optoelectronic corrosion resistance, and breakthroughs are urgently needed. Summary of the Invention

[0006] The purpose of this invention is to overcome the shortcomings of the prior art and provide a highly dispersed and strongly bonded ZIF-67-derived Co3S4 quantum dot composite TiO2 heterojunction optoelectronic material, its preparation method, and its application.

[0007] To achieve the above objectives, the technical solution of the present invention is as follows: A method for preparing a ZIF-67-derived Co3S4 quantum dot composite TiO2 heterojunction optoelectronic material. Step 1, Preparation of ZIF-67 powder material: Cobalt nitrate hexahydrate (Co(NO3)2·6H2O) and hexadecyltrimethylammonium bromide (C 16 H 33 (CH3)3NBr) was dissolved in deionized water to prepare solution A; 2-methylimidazole was dissolved in deionized water to prepare solution B; solution A was slowly added dropwise to solution B under magnetic stirring, and the mixture was dried under vacuum to obtain the ZIF-67 precursor. Step 2, Preparation of Co3S4 quantum dot materials: The ZIF-67 precursor was dispersed in anhydrous ethanol, thioacetamide (TAA) was added, and after stirring evenly, it was transferred to a reaction vessel for hydrothermal reaction to obtain a solid intermediate. The intermediate was placed in a tube furnace and calcined at 350 °C for 2 h under nitrogen to complete sulfidation and crystallization, thus obtaining Co3S4 quantum dot material. Step 3: Prepare the Co3S4 / TiO2 composite material and composite photoanode: The Co3S4 quantum dot material obtained above was added to deionized water and ultrasonically dispersed to form a uniform suspension. Then, commercial TiO2 powder (P25 type TiO2 powder) was added to the suspension and ultrasonically dispersed to mix the two phases evenly. The mixed suspension was transferred to a reactor and reacted at 85 °C for 12 h to obtain the Co3S4 / TiO2 composite material.

[0008] The Co3S4 / TiO2 composite material was added to ethanol and ultrasonically dispersed for 15 min. Then, Nafion solution was added, and the mixed solution was uniformly coated on an FTO conductive glass sheet to obtain a composite photoanode. The mass of the composite material was 0.002 g, and the volume of the Nafion solution was 0.1 mL.

[0009] In step 1, solution A is slowly added dropwise to solution B under magnetic stirring, and stirring is continued for 20 min. The resulting product is centrifuged, washed with deionized water and anhydrous ethanol, and dried in a vacuum drying oven at 60 °C to obtain the ZIF-67 precursor. Solution A contains Co(NO3)2·6H2O, C... 16 H 33 The mass ratio of (CH3)3NBr to water is 30:1:1000; the mass ratio of C4H6N2 to water in solution B is 220:3500; the mass ratio of solution A to solution B is 1:6-8.

[0010] In step 2, the hydrothermal reaction is carried out at 120 °C for 4 h. After naturally cooling to room temperature, the product is centrifuged, washed and dried to obtain a solid intermediate. The mass ratio of ZIF-67 precursor, anhydrous ethanol and TAA is 3:12800:50.

[0011] In step 3 shown, the mass ratio of Co3S4, TiO2 powder and water is 1:1 to 4:100.

[0012] A ZIF-67-derived Co3S4 quantum dot composite TiO2 heterojunction optoelectronic material prepared by the method described herein, wherein the ZIF-67-derived Co3S4 quantum dot / TiO2 heterojunction optoelectronic composite material prepared by the method described herein is characterized in that uniformly sized Co3S4 quantum dots are in a highly dispersed in-situ anchored state on the surface of a TiO2 substrate, and a disordered interface layer with strong atomic-level chemical bonding is formed at the interface between the two phases.

[0013] Application of the ZIF-67-derived Co3S4 quantum dot composite TiO2 heterojunction optoelectronic material, and its application in photogenerated cathode protection.

[0014] The present invention has the following beneficial effects: This invention effectively solves the technical challenges of easy aggregation, weak interfacial bonding, and easy detachment of quantum dots by achieving in-situ uniform anchoring of zero-dimensional Co3S4 quantum dots on the TiO2 surface. Utilizing the excellent bandgap matching of the two materials to construct a highly efficient heterojunction, it significantly broadens the spectral response range while greatly accelerating the directional migration and separation of photogenerated carriers at the interface. This provides a new photogenerated cathodic protection strategy for stainless steel and other metal structural components in marine environments, offering both high photoelectric corrosion resistance and long-term stability. Specifically: 1. A highly active and highly dispersed interface was constructed. This invention ingeniously employs an in-situ chemical modification strategy to successfully achieve highly uniform dispersion of Co3S4 quantum dots on the TiO2 surface. This effectively overcomes the technical bottleneck of traditional quantum dots, which are prone to self-aggregation due to high surface energy, leading to the loss of active sites. The highly dispersed Co3S4 quantum dots not only retain their unique zero-dimensional quantum size effect, significantly increasing the specific surface area for photoelectrochemical reactions, but also provide extremely high-density active sites for interfacial transport of photogenerated carriers, significantly improving the material's fundamental photoelectric response sensitivity.

[0015] 2. Significantly suppresses photogenerated carrier recombination This invention constructs a Co3S4 / TiO2 heterojunction system with a matched band structure. Utilizing the relatively negative conduction band potential of Co3S4 quantum dots, a highly efficient directional charge transport channel is formed between the Co3S4 quantum dots and TiO2. Under the strong driving force of the built-in electric field of the formed type II (also pn-type) heterojunction, photogenerated electrons can achieve rapid directional migration and efficient separation across the interface, significantly reducing the probability of secondary recombination of internal electron-hole pairs. The composite photoanode prepared by this invention exhibits a significantly higher transient photocurrent density and carrier concentration than pure TiO2, resulting in a qualitative leap in the output and utilization efficiency of photogenerated electrons.

[0016] 3. Significantly broadens the spectral response range and greatly improves the utilization efficiency of visible light. This invention successfully redshifts the absorption boundary of the composite optoelectronic material significantly into the visible light region by introducing narrow-bandgap Co3S4 quantum dots for synergistic modification. This significantly enhances the absorption coefficient and energy capture capability of the material for visible light, enabling the material to make fuller use of abundant solar resources.

[0017] 4. Establishes a robust chemical bonding interface, exhibiting excellent long-term corrosion resistance and stability. This invention enables the formation of strong chemical bonds between Co3S4 quantum dots and a TiO2 substrate through in-situ growth. This tight atomic-level interfacial contact not only greatly reduces interfacial charge transfer impedance but also endows the material with excellent mechanical stability and chemical corrosion resistance. In long-term simulated marine environment cycling tests, the quantum dots showed no significant detachment or deactivation, ensuring long-term and stable photocathode protection for stainless steel and other metal structural components.

[0018] Therefore, by constructing a Co3S4 quantum dot-modified TiO2 (Co3S4 / TiO2) composite material with ordered structure, controllable size, and tight interfacial contact, this invention not only broadens the spectral response range but also significantly optimizes the migration path of photogenerated carriers and suppresses their recombination, providing a new technical strategy for the design and application of next-generation high-performance photogenerated cathodic protection materials. Attached Figure Description

[0019] Figure 1 This is a schematic diagram of the preparation of Co3S4 / TiO2 composite material, showing the in-situ growth of Co3S4 quantum dots on the surface of TiO2 particles.

[0020] Figure 2 Scanning electron microscope (SEM) images of different samples: (a) commercial TiO2 powder; (b) pure Co3S4 quantum dot powder; (c) Co3S4 / TiO2 composite powder.

[0021] Figure 3 The following are the TEM and HRTEM characterization results of the Co3S4 / TiO2 composite powder (a) and (b) and the corresponding FFT diffraction spectra (c) and (d).

[0022] Figure 4 Characterization of specific surface area and pore structure of pure TiO2 and Co3S4 / TiO2 heterojunction materials: (a) N2 adsorption-desorption isotherm (BET); (b) pore size distribution curve.

[0023] Figure 5 The image shows the Raman spectrum of the TiO2 and Co3S4 / TiO2 composite material.

[0024] Figure 6 Optical properties characterization of Co3S4, TiO2 and Co3S4 / TiO2 composites: (a) UV-vis DRS curves; (b) Tauc plot transformation curves of the corresponding samples.

[0025] Figure 7 The steady-state fluorescence emission spectra of TiO2 and Co3S4 / TiO2 composite materials are shown.

[0026] Figure 8 This is a schematic diagram of the apparatus used for (a) open-circuit potential and electrochemical impedance spectroscopy testing and (b) photocurrent density testing.

[0027] Figure 9 The figures show (a) open-circuit potential variation curves of 304 SS coupled with pure TiO2 or different proportions of Co3S4 / TiO2 photoanodes under intermittent visible light irradiation; (b) comparison of photogenerated potential variation values ​​of different photoanodes; and (c) photocurrent density variation curves.

[0028] Figure 10 The graph shows the open-circuit potential change after 16 hours of photoanode coupling of 304 SS and CT2 under intermittent visible light irradiation.

[0029] Figure 11The CV curves of (a) TiO2 and (b) Co3S4 / TiO2 at different scan rates; and the ECSA of (c) TiO2 and (d) Co3S4 / TiO2.

[0030] Figure 12 (a) Nyquist plot of 304 SS coupled with different Co3S4 / TiO2 samples under visible light irradiation; (b) and (c) Bode plots. Detailed Implementation

[0031] To further clarify the technical solution of the present invention, the specific structure, preparation process, and performance of the present invention are described below with reference to the accompanying drawings through typical embodiments. However, the present invention is not limited to the following embodiments, and all equivalent transformations and improvements made based on the concept of the present invention should be covered within the protection scope of the present invention.

[0032] The material of this invention is a metal-organic framework material, zeolite imidazole framework-67 (ZIF-67), which is self-assembled from cobalt ions and imidazole ligands. ZIF-67 possesses high specific surface area, controllable morphology, and ease of synthesis. Furthermore, Co3S4 quantum dots derived from ZIF-67 exhibit unique size effects and abundant surface active sites, and their conduction band position is relatively negative, enabling ideal band matching with TiO2. By constructing a Co3S4 / TiO2 heterojunction and utilizing an internal electric field to drive directional electron migration, it is expected to significantly improve the material's electron transport capability and photogenerated cathodic protection effect.

[0033] Example 1 Preparation repeated as Figure 1 As shown, Step 1, Preparation of ZIF-67 powder material: 0.291 g of Co(NO3)2·6H2O was dissolved in 10 mL of deionized water containing 10 mg of hexadecyltrimethylammonium bromide, denoted as solution A; 4.54 g of 2-methylimidazole was dissolved in 70 mL of deionized water, denoted as solution B. Solution A was slowly added dropwise to solution B while stirring. After centrifugation, the product was washed repeatedly with deionized water and anhydrous ethanol, and then dried in a vacuum drying oven to obtain ZIF-67 powder.

[0034] Step 2, Preparation of Co3S4 quantum dot materials: 3 mg of ZIF-67 powder was added to 15 mL of anhydrous ethanol, followed by 50 mg of TAA. After stirring thoroughly, the mixture was transferred to a polytetrafluoroethylene-lined hydrothermal reactor and reacted at 120 °C for 4 h. After the reactor cooled naturally to room temperature, the product was centrifuged, washed, and dried to obtain solid C. Then, solid C was calcined in a tube furnace at 350 °C for 2 h under a nitrogen atmosphere to obtain Co3S4 quantum dot materials.

[0035] Step 3, Preparation of Co3S4 / TiO2 composite material: 1 g of Co3S4 powder was added to 100 mL of deionized water and ultrasonically dispersed for 2 h to form a uniform suspension. Then, 1 g of commercial TiO2 powder (P25 type TiO2 powder) was added to the suspension, and ultrasonic dispersion was continued for 1 h to ensure uniform mixing of the two phases. The mixed suspension was transferred to a reaction vessel lined with polytetrafluoroethylene and reacted at 85 °C for 12 h. The resulting product was centrifuged, washed alternately with deionized water and anhydrous ethanol, and dried in a forced-air drying oven at 60 °C to obtain the Co3S4 / TiO2 composite material, which was labeled CT1. When the mass ratio of Co3S4 powder to TiO2 powder was 1:2, 1:3, and 1:4, the resulting samples were labeled CT2, CT3, and CT4, respectively.

[0036] Step 4, Preparation of Co3S4 / TiO2 composite photoanode: 0.002 g of Co3S4 / TiO2 composite material was added to ethanol and ultrasonically dispersed for 15 min. Then, 0.1 mL of Nafion solution was added, and the mixture was uniformly coated onto an FTO conductive glass sheet to obtain a composite photoanode.

[0037] Characterization and performance testing of photoanodes: 1. Characterization of photoanodes like Figure 2 As shown in a, pure TiO2 particles exhibit a regular polyhedral structure with a particle size of approximately 100-200 nm, a smooth surface, and excellent crystallinity. Figure 2 b shows the morphology of Co3S4 derived from the ZIF-67 precursor, which exhibits a high specific surface area of ​​ultrafine nanoparticle aggregates with abundant porous network channels. When Co3S4 quantum dots are introduced to modify TiO2, the Co3S4 / TiO2 composite material maintains the original basic framework, but the particle surface becomes significantly rougher due to the in-situ anchoring of zero-dimensional quantum dots, and the interparticle interface contact becomes more compact. Figure 2 c). This optimized micro / nano structure not only increases the electrochemical active area and exposes more catalytic active sites, but also constructs a continuous and rapid transport channel for the cross-interface migration of photogenerated carriers, thereby contributing to a significant improvement in the protection performance of photogenerated cathodic protection.

[0038] Figure 3 TEM images of a show that the smaller Co3S4 nanophases are firmly and tightly attached to the surface of the larger polyhedral TiO2 particles. Figure 3In the HRTEM image of b, two highly detailed two-dimensional lattice fringes can be clearly observed. The upper region has a lattice spacing of 0.283 nm, belonging to the (311) plane of the cubic Co3S4 phase; the lower substrate region has a lattice spacing of 0.351 nm, corresponding to the (101) plane of the anatase TiO2 phase. Notably, a distinct nanoscale disordered interface layer is formed at the boundary between the two phases, indicating that Co3S4 and TiO2 achieve atomic-level chemical bonding through strong interfacial interactions. Meanwhile, Figure 3 c and 3d are Fast Fourier Transform (FFT) images of the corresponding micro-regions. The sharp and highly symmetrical digital micro-region electron diffraction spots further confirm the excellent crystallinity of each component of the composite material. This atomically close-contact heterostructure and high crystallinity significantly reduce the cross-interface charge transfer impedance, creating a high-speed, directional gliding channel for photogenerated electrons under the drive of the built-in electric field. This fundamentally suppresses secondary recombination of charge carriers, providing a microstructural guarantee for its excellent photogenerated cathodic protection performance.

[0039] Figure 4 The results show that both the original TiO2 and the Co3S4 / TiO2 composite exhibit typical type IV nitrogen adsorption-desorption isotherms and type H3 hysteresis loops, indicating the presence of abundant mesoporous structures in the materials, with pore sizes mainly distributed between 2 and 100 nm. Under the same relative pressure (P / P0), the maximum adsorption capacity of pure TiO2 is 25 cm⁻¹. 3 / g, while after loading Co3S4, the maximum adsorption capacity of the composite material was significantly increased to 105 cm⁻¹. 3 / g, accompanied by a wider pore size distribution and a larger pore volume. Quantitative analysis results show that the specific surface area (S) of the original TiO2 is... BET The value is 2.32 m. 2 / g, while the specific surface area of ​​the composite material reaches 8.96 m². 2 / g, an increase of nearly four times ( Figure 4 (b) This indicates that loading Co3S4 quantum dots can effectively increase the specific surface area of ​​the TiO2 substrate. Furthermore, after introducing Co3S4, the average pore size of the material slightly decreased from 16.36 nm to 14.45 nm. This change is mainly due to the deposition of tiny Co3S4 quantum dots on the surface of the mesoporous TiO2 substrate, filling larger pores or partially restricting the channels. This unique heterostructure exposes more active sites, enhances the adsorption capacity of reactant molecules, and accelerates the migration and separation of photogenerated carriers, thus significantly improving the photogenerated cathodic protection performance.

[0040] like Figure 5 As shown, for pure TiO2 samples, at 142, 392, 512, and 636 cm⁻¹...-1 The distinct scattering peaks observed at the locations are clearly attributed to the E values ​​characteristic of anatase TiO2. g B 1g A 1g +B 1g , and E g Vibration modes. In the Co3S4 / TiO2 composite, in addition to the significant vibrational peak of TiO2, a vibrational peak was also detected at 648 cm⁻¹. -1 The novel characteristic peak at this location corresponds to the A of Co3S4. 1g Vibrational modes. The above results confirm the coexistence of these two phases and verify the successful preparation of Co3S4 / TiO2 nanocomposites.

[0041] 2. Light absorption performance and photoelectric conversion capability of photoanodes like Figure 6 As shown in Figure a, the light absorption of pure TiO2 is mainly concentrated in the ultraviolet region with wavelengths less than 380 nm, and its visible light trapping ability is extremely weak. In contrast, pure Co3S4 exhibits strong broad-spectrum absorption characteristics across the entire ultraviolet-visible region (250~800 nm). When Co3S4 quantum dots are combined with TiO2, the light absorption boundary of the Co3S4 / TiO2 heterojunction material undergoes a significant redshift, and the absorption intensity in the visible light region is greatly enhanced. Furthermore, the band gap (E) of the material is further analyzed using the Tauc relation. g Tangent extrapolation calculations were performed, and the results are as follows: Figure 6 As shown in b, the band gap energies of pure Co3S4 and pure TiO2 are 1.80 eV and 3.08 eV, respectively. The effective band gap energy of the modified Co3S4 / TiO2 composite material was successfully reduced to 2.62 eV. These changes in optical properties clearly demonstrate the spectral modification effect of zero-dimensional Co3S4 quantum dots on the TiO2 substrate. The narrowing of the band gap allows the composite photoanode to more fully absorb and utilize the visible light component of sunlight, generating a higher density of photogenerated carriers under illumination conditions, thus laying a solid optical dynamics foundation for its high-performance photogenerated cathode protection in marine environments.

[0042] like Figure 7As shown, pure TiO2 exhibits a strong and broad fluorescence emission peak in the 450–700 nm range, indicating that the electrons and holes generated internally tend to undergo rapid radiative recombination, which greatly limits its photoelectric conversion efficiency. In contrast, when modified with Co3S4 quantum dots, the fluorescence emission intensity of the Co3S4 / TiO2 composite material shows a remarkably sharp drop. This strong fluorescence quenching phenomenon clearly indicates that the efficient heterojunction and atomically close interface successfully constructed between Co3S4 and TiO2 provide a convenient directional migration channel for photogenerated carriers. Driven by the built-in electric field, photogenerated electrons can be separated and transported across the interface in a timely manner, thereby fundamentally suppressing the secondary recombination of carriers.

[0043] 3. Photogenerated cathodic protection performance test For open-circuit potential change curves and electrochemical impedance spectroscopy measurements, use Figure 8 The dual electrolytic cell system shown in figure a was tested. Different prepared photoanodes were placed in a photolytic cell containing 0.1 mol / L Na₂S and 0.2 mol / L NaOH solutions, while the 304 stainless steel to be protected was placed in a corrosion cell containing 3.5% NaCl solution. The photoanode material was connected to the metal to be protected as the working electrode, a platinum sheet as the counter electrode, and a saturated calomel solution as the reference electrode. The photocurrent density change curve was measured using the following method: Figure 8 As shown in diagram b, the photoanode material is used as the working electrode, the protected metal is grounded, and the reference and counter electrodes are short-circuited by a wire. The light source is provided by a 300 W xenon lamp equipped with a 420 nm filter, which illuminates the photoanode material perpendicularly through a quartz window in the electrolytic cell. Cyclic voltammetry (CV) curves of the prepared photoanode material were tested using the most common three-electrode system at scan rates of 10, 20, 30, 40, 50, and 60 mV / s.

[0044] Depend on Figure 9 As can be seen, the initial self-corrosion potential of untreated 304 stainless steel is approximately -156 mV vs. SCE. By constructing composite materials, all samples effectively delayed the corrosion process of 304 stainless steel. Among them, the CT2 sample exhibited the best corrosion resistance, with its coupling potential under illumination showing a significant negative shift compared to the substrate, reaching a maximum of 718 mV vs. SCE. This is mainly attributed to the excellent photoelectric conversion efficiency of the CT2 sample, confirming the unique advantages of this composite nanostructure design in enhancing optical absorption and corrosion resistance. Figure 9b) visually presents the differences in photogenerated potential changes among different material systems using a scatter plot. The pn-type Co3S4 / TiO2 photoanode constructed in this invention achieves a photogenerated potential change of 718 mV vs. SCE, which is higher than that of materials reported in the literature such as WO3-TiO2-BiVO4 (600 mV), TiO2 / ZnSe (508 mV), and Co3S4@ZnO (520 mV), demonstrating significant performance advantages. Figure 9 As can be seen from c, during the initial stage of visible light irradiation, the photocurrent density of the Co3S4 / TiO2 composite material rapidly increased, then stabilized and reached the maximum saturation photocurrent value. Among all the test samples, the composite material labeled CT2 exhibited the highest photocurrent response peak. This indicates that the CT2 composite material has the best charge separation and transport efficiency, and its photoelectric conversion performance is significantly improved compared to other comparative materials.

[0045] The stability of the prepared material under photogenerated cathodic protection was also tested in this embodiment of the invention, and its potential-time curve is shown below. Figure 10 As shown, when the 304 stainless steel is coupled with the Co3S4 / TiO2 composite photoanode prepared in this invention, the system potential decreases to approximately -700 mV vs. SCE even in the dark. Under periodic illumination, the system potential instantaneously polarizes to -880 mV vs. SCE. During continuous electrochemical monitoring for up to 16 hours, the coupling potential curve shows a stable straight line with minimal potential fluctuations, remaining consistently within a safe protection range far below the self-corrosion potential of stainless steel. These experimental results definitively confirm that the Co3S4 / TiO2 composite nanostructure provided by this invention possesses significant photogenerated cathodic protection durability, providing long-term and stable anti-corrosion protection for metal substrates.

[0046] Figure 11 a and Figure 11 b shows the CV curves of the prepared CT2 and pure TiO2 at different scan rates. A larger CV closure area indicates more active sites and stronger charge storage capacity. Both the CV closure area and response current of the two samples increase with increasing scan rate, exhibiting typical capacitive response characteristics. The CV area of ​​CT2 is significantly larger than that of pure TiO2, with a maximum response current of approximately 19 mA·cm⁻¹. -2 It is approximately equal to pure TiO2 (3.5 mA·cm⁻¹). -2 The integral area is 5 times that of the scan rate. The integral area shows a good linear relationship with the scan rate, indicating stable charge storage. The integral area of ​​pure TiO2 is only 1.32~1.63 mA·V·cm. -2 CT2 increased from 9.0 to 11.1 mA·V·cm. -2The fitting slope of CT2 is much greater than that of pure TiO2, indicating that it has a higher specific capacitance and a larger electrochemical active surface area. This proves that the addition of Co3S4 increases the specific surface area and active sites, promotes the migration of photogenerated electrons, and the higher specific capacitance allows it to release electrons in the dark, providing continuous cathodic protection.

[0047] Figure 12 a is the Nyquist plot of the sample. Pure TiO2 exhibits the largest semicircular radius, indicating its interfacial charge transfer resistance (R0). ct The high Rc makes secondary recombination of charge carriers highly likely at the interface. After introducing Co3S4 quantum dots to construct heterojunction composite materials (samples CT1 ~ CT4), the radius of curvature of the samples all showed significant shrinkage to varying degrees. Among them, sample CT2 exhibited the smallest semi-circular radius, which means that this sample has the lowest Rc. ct This conclusion is in Figure 12 The Bode plots for b and 12c further confirm this. In the low-frequency region (10... -2 At Hz, the CT2 sample exhibits the lowest impedance modulus and a significantly reduced peak phase angle. This systematic improvement in impedance performance clearly demonstrates that the successful modification of the zero-dimensional Co3S4 quantum dots and the strong interaction formed between the two phase interfaces successfully constructed a low-impedance, high-velocity directional electron gliding channel within the composite material. Driven by the built-in electric field, the R0 across the interface... ct The photogenerated electrons were suppressed to the greatest extent, thus significantly accelerating the directional separation and outflow of photogenerated electrons. This kinetic evidence perfectly corroborates the above PL and UV-vis DRS results, elucidating from an electrochemical perspective the intrinsic mechanism by which all TiO2-based composite materials can effectively delay the corrosion process of 304 stainless steel, with the CT2 sample exhibiting the best performance.

[0048] In summary, this invention successfully developed a zero-dimensional Co3S4 quantum dot-modified TiO2 composite photoanode (Co3S4 / TiO2) using the zeolite imidazole framework-67 precursor. This addresses the bottlenecks of traditional photoanodes, such as narrow spectral response, fast carrier recombination, and easy aggregation and detachment of quantum dots. Microscopic characterization confirmed that uniformly sized Co3S4 quantum dots are highly dispersed and in-situ anchored on the TiO2 surface. The atomically strong chemically bonded disordered interface layer formed at the two-phase interface fundamentally overcomes the poor contact defects of traditional physical mixing interfaces. Due to the introduction of quantum dots, the specific surface area of ​​the composite material increases from 2.32 m² / g. 2 / g significantly increased to 8.96 m 2The composite material, with a density of approximately 1.5 g, exposes an extremely high density of active sites for photoelectrochemical reactions. Simultaneously, the narrow bandgap Co3S4-induced absorption boundary exhibits a significant redshift, reducing the effective bandgap to 2.62 eV, enabling efficient capture of visible light. The ideal bandgap matching of the heterojunction creates a highly efficient built-in electric field, resulting in strong fluorescence quenching and a sharp drop in the Nyquist radius and low-frequency impedance modulus. This drives photogenerated electrons to migrate rapidly and directionally along the low-impedance channel, effectively suppressing secondary recombination of charge carriers in space. In simulated marine environments, this composite material effectively delays the oxidation and corrosion process of 304 stainless steel, with the CT2 sample exhibiting the best performance and a maximum protection potential change of 718 mV. This material combines energy saving, long-lasting performance, and environmental friendliness, providing a promising new strategy for the design of photogenerated cathodic protection for next-generation marine infrastructure.

Claims

1. A method for preparing a ZIF-67-derived Co3S4 quantum dot composite TiO2 heterojunction optoelectronic material, characterized in that, Step 1, Preparation of ZIF-67 powder material: Cobalt nitrate hexahydrate (Co(NO3)2·6H2O) and hexadecyltrimethylammonium bromide (C 16 H 33 (CH3)3NBr) was dissolved in deionized water to prepare solution A; 2-methylimidazole was dissolved in deionized water to prepare solution B; solution A was slowly added dropwise to solution B under magnetic stirring, and the mixture was dried under vacuum to obtain the ZIF-67 precursor. Step 2, Preparation of Co3S4 quantum dot materials: The ZIF-67 precursor was dispersed in anhydrous ethanol, thioacetamide (TAA) was added, and after stirring evenly, it was transferred to a reaction vessel for hydrothermal reaction to obtain a solid intermediate. The intermediate was placed in a tube furnace and calcined at 350 °C for 2 h under nitrogen to complete sulfidation and crystallization, thus obtaining Co3S4 quantum dot material. Step 3: Prepare the Co3S4 / TiO2 composite material and composite photoanode: The Co3S4 quantum dot material obtained above was added to deionized water and ultrasonically dispersed to form a uniform suspension. Then, commercial TiO2 powder (P25 type TiO2 powder) was added to the suspension and ultrasonically dispersed to mix the two phases evenly. The mixed suspension was transferred to a reactor and reacted at 85 °C for 12 h to obtain the Co3S4 / TiO2 composite material.

2. The preparation method of the ZIF-67-derived Co3S4 quantum dot composite TiO2 heterojunction optoelectronic material according to claim 1, characterized in that, The Co3S4 / TiO2 composite material was added to ethanol and ultrasonically dispersed for 15 min. Then, Nafion solution was added, and the mixed solution was uniformly coated on an FTO conductive glass sheet to obtain a composite photoanode.

3. The preparation method of the ZIF-67-derived Co3S4 quantum dot composite TiO2 heterojunction optoelectronic material according to claim 1, characterized in that, In step 1, solution A is slowly added dropwise to solution B under magnetic stirring, and stirring is continued for 20 min. The resulting product is centrifuged, washed with deionized water and anhydrous ethanol, and dried in a vacuum drying oven at 60 °C to obtain the ZIF-67 precursor. Solution A contains Co(NO3)2·6H2O, C... 16 H 33 The mass ratio of (CH3)3NBr to water is 30:1:1000; the mass ratio of C4H6N2 to water in solution B is 220:3500; the mass ratio of solution A to solution B is 1:6-8.

4. The preparation method of the ZIF-67-derived Co3S4 quantum dot composite TiO2 heterojunction optoelectronic material according to claim 1, characterized in that, In step 2, the hydrothermal reaction is carried out at 120 °C for 4 h. After naturally cooling to room temperature, the product is centrifuged, washed and dried to obtain a solid intermediate. The mass ratio of ZIF-67 precursor, anhydrous ethanol and TAA is 3:12800:

50.

5. The method for preparing the ZIF-67-derived Co3S4 quantum dot composite TiO2 heterojunction optoelectronic material according to claim 1, characterized in that, In step 3 shown, the mass ratio of Co3S4, TiO2 powder and water is 1:1 to 4:

100.

6. A ZIF-67-derived Co3S4 quantum dot composite TiO2 heterojunction optoelectronic material prepared by the method of claims 1-5, characterized in that: The ZIF-67-derived Co3S4 quantum dot / TiO2 heterojunction optoelectronic composite material was prepared according to the method described in claim 1.

7. The application of the ZIF-67-derived Co3S4 quantum dot composite TiO2 heterojunction optoelectronic material as described in claim 6, characterized in that: Application of ZIF-67-derived Co3S4 quantum dot composite TiO2 heterojunction optoelectronic materials in photogenerated cathode protection.